On the Construction of Cluster Systolic Arrays - Davtyan, Edmon M. (Mathematical Problems of Computer Science, 2024)
The paper presents three approaches to the construction of cluster systolic arrays. A careful analysis of these approaches based on the comparison of the running times of corresponding systolic arrays was carried out. A method to minimize the running time is proposed.